How to Improve Our Pending Global Village by Application of Novel Economic Instruments - Jan Stenis (New Innovations in Economics, Business and Management Vol. 7, 2022)
Objectives: There is a general effort to gain desired outcomes with as few resources as possible. There is a need for ever more cost-effective organisations, making this study required to improve the policy efficiency and raise the technological standard in various communities within the global market. That facilitates local enterprises’ competing with global corporations when the boundaries are dissolved across national cultures and economies in the pending Global Village. The Naturally Optimised Revenue Demand in Communities (NORDIC) model is employed to improve the flow of physical and intangible utilities through entities of different kinds, such as producing companies and nations. The applied economic instrument also improves the ecological footprint of organisations. Methods: The basis for the work is the existing Efficient Use of Resources for an Optimal Production Economy (EUROPE) model, which is developed to become more powerful. Constructed shadow costs are added to the bookkeeping systems of organisations to give economic incentives to improve the economy, technology, and environment. The design of the scientific work emphasises a logical-historical disposition. Results: The NORDIC model gives managers a management tool. The model is applicable to the public sector and commercial activities. The method provides a key indicator to assess and improve actors’ performance. A manual for the practical use of the NORDIC model is presented. The case study demonstrates how to create an economic incentive to reduce costs and increase efficiency in Sweden’s health care, education, and social services. Conclusions: The model shows utility for various entities, such as public sectors, within nations. Citizens of the ever more integrated global market get a better life, and improved health, due to a better economy when the results in this study are implemented. In the future, studies could be conducted to determine how the NORDIC model can be applied to larger units. There is potential to apply the model to the global context.